Impact of cover crops and nitrogen application on nitrous oxide fluxes and grain yield of sorghum and maize - Mahama, George Yakubu (Kansas State University, 2015)
Leguminous cover crops systems have been envisaged as a critical component of sustainable agriculture due to their potential to increase soil productivity through cycling of carbon (C) and nitrogen (N) in agricultural systems. The objectives of this study were to evaluate the performance of leguminous summer cover crops; cowpea [Vigna unguiculata (L.) Walp.], pigeon pea [Cajanus cajan (L.) Millsp], sunn hemp (Crotalaria juncea L.) and double-cropped grain crops; grain sorghum [Sorghum bicolor (L.) Moench] and soybean [Glycine max (L.) Merr.] after winter wheat (Triticum aestivum L.) and to determine the effects of these crops and varying N rates in the cropping system on nitrous oxide (N[subscript]2O) emissions, growth and yield of succeeding grain sorghum and maize (Zea mays L.) crop, soil aggregation, aggregate-associated C, and N. Field and laboratory studies were conducted for two years. The cover crops and double-cropped grain crops were planted immediately after winter wheat harvest. The cover crops were terminated at the beginning of flowering. Nitrogen fertilizer (urea 46% N) rates of 0, 45, 90, 135, and 180 kg N ha[superscript]-1 were applied to grain sorghum or maize in fallow plots. Pigeon pea and grain sorghum had more C accumulation than cowpea, sunn hemp and double-cropped soybean. Pigeon pea and cowpea had more N uptake than sunn hemp and the double-cropped grain crops. Fallow with N fertilizer application produced significantly greater N[subscript]2O emissions than all the cover crops systems. Nitrous oxide emissions were relatively similar in the various cover crop systems and fallow with 0 kg N ha[superscript]-1. Grain yield of sorghum and maize in all the cover crop and double cropped soybean systems was similar to that in the fallow with 45 kg N ha[superscript]-1. Both grain sorghum and maize in the double-cropped soybean system and fallow with 90 kg N ha[superscript]-1 or 135 kg N ha[superscript]-1 gave profitable economic net returns over the years. The double-cropped grain sorghum system increased aggregate-associated C and whole soil total C, and all the cover crop and the double-cropped soybean systems increased aggregate-associated N and soil N pools. Inclusion of leguminous cover crops without N fertilizer application reduced N[subscript]2O emissions and provided additional C accumulation and N uptake, contributing to increased grain yield of the following cereal grain crop.
Keywords: Cover crops; Nitrogen fertilizers; Sustainable agriculture; Agronomy (0285)